Factors Influencing Investment Decisions among College Students: A Comparative Analysis Between India & Nigeria - KARAMCHANDANI, DEVANSHU (AIBPM Publisher, 2024)
Investment is done for the purpose to gain profitable returns. Investing in a well-diversified portfolio offers a multitude of benefits, including capital appreciation to grow wealth over time. As a student, managing finance can be challenging, but exploring opportunities for passive income can make a significant difference in financial stability and independence. Moreover, strategic investments can provide tax benefits that help optimize your financial situation. When considering the expected returns, it's crucial to balance them with liquidity for easy access to funds when needed, ensuring financial security. Additionally, a diversified approach with investment type contributes to risk minimization, safeguarding your investments against market volatility and potential losses. Overall, these elements collectively form a robust strategy to secure your financial future. This study endeavors to comparatively analyze the factors influencing investment decisions among college students in India and Nigeria. Demographics play a pivotal role in shaping investment choices, and understanding the differences in the attitude of these countries is vital for effective financial education initiatives